(untitled) (Fiep Bulletin - online, 2014)
This study was carried out aiming some purposes, such as, to analyse the facilities provided for recreational physical activities and the distribution of time in children´s education. It was characterized as a case of a study, realized in level IV at a Children´s Education Centre in Campo Grande in the state of Mato Grosso do Sul . The systematized observation was adopted as the methodology of investigation and the information was registered in a field diary. The results showed that the institution which was analysed does not have specific facilities for practicing the hand - eye coordination activities, therefore children have to spend their school time inside the classrooms . Regarding to the distribution of time in their school daily lives ,they stay at the Children´s Education Centre for 10h30m,d istributed to one hour in the morning (they are supposed to wait for the other students), four hours and twenty minutes to care activities (food , personal hygiene , sleep) and five hours and ten minutes to literacy activities, art education, recreation and other activities chosen by the students in return for tasks asked by the teachers. All in all, it is easy to say that the institution needs more facilities to be used by the students to develop their hand - eye coordination at once, based on the importance of this skill at this age for them to achieve a good level of this coordination when they get mature enabling them to realize sporting movements. In addition to this, the distribution of time should be given special attention, because children remain sitting for too long waiting for their classmates to come.